Vaccine-Associated Disease Enhancement (VADE): Considerations in Postvaccination COVID-19. (29th October 2021) - Tunjungputri, Rahajeng N.; Tetrasiwi, Erpryta Nurdia; Veronica, Merlinda; Pandelaki, Jacub; Ibrahim, Fera; Nelwan, Erni Juwita
Abstract : Introduction . The COVID-19 pandemic has entered a new phase with the roll-out of several vaccines worldwide at an accelerated phase. The occurrence of a more severe presentation of COVID-19 after vaccination may affect policymakers' decision-making and vaccine uptake by the public. Vaccine-associated disease enhancement (VADE) is the modified presentation of infections in individuals after having received a prior vaccination. Currently, little is known about the potential of vaccine-associated disease enhancement (VADE) following COVID-19 immunization. Case Illustration . We herewith report two patients admitted with confirmed COVID-19 pneumonia with a history of CoronaVac vaccination. The first patient with a relatively milder course of the disease had received two doses of CoronaVac, whereas the second patient with a more progressive course of the disease received only one dose before developing symptoms and being admitted to the hospital. Our observations suggest that vaccination could act in boosting the inflammatory process and reveal the previously asymptomatic COVID-19 illness. Theoretically, vaccines could induce VADE, where only suboptimal, nonprotective titers of neutralizing antibodies were produced or proinflammatory T-helper type 2 response was induced. Secondly, enhanced respiratory disease (ERD) could manifest, where pulmonary symptoms are more severe due to peribronchial monocytic and eosinophilic infiltration. Understanding VADE is important for the decision-making by the public, clinicians, and policymakers and is warranted for successful vaccination uptake. Conclusion . We report two cases of patients developing COVID-19 shortly after CoronaVac vaccination in which VADE is likely. We recommend that current vaccination strategies consider the measurement of neutralizing antibody titer as a guide in ensuring the safest strategy for mass immunization. Studies are needed to investigate the true incidence of VADE on vaccinated individuals as well as on how to differentiate between VADE and severe manifestations of COVID-19 that are unrelated to vaccination.